1997
DOI: 10.1086/301644
|View full text |Cite
|
Sign up to set email alerts
|

Peutz-Jeghers Syndrome: Confirmation of Linkage to Chromosome 19p13.3 and Identification of a Potential Second Locus, on 19q13.4

Abstract: Peutz-Jeghers syndrome (PJS) is an autosomal dominant disease with variable expression and incomplete penetrance, characterized by mucocutaneous pigmentation and hamartomatous polyposis. Patients with PJS have increased frequency of gastrointestinal and extraintestinal malignancies (ovaries, testes, and breast). In order to map the locus (or loci) associated with PJS, we performed a genomewide linkage analysis, using DNA polymorphisms in six families (two from Spain, two from India, one from the United States,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
95
0
9

Year Published

1999
1999
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(104 citation statements)
references
References 20 publications
0
95
0
9
Order By: Relevance
“…First, inactivating mutations that either truncate or disrupt the kinase activity of the protein encoded by this gene are detected in the majority but not all cases of PJS. [6][7][8][60][61][62][63][64][65][66][67][68][69] Second, dominant inheritance of a mutant STK11/LKB1 allele coupled with LOH or somatic mutation of the remaining wild-type STK11/LKB1 allele has been documented in PJS patients with various malignancies. 10,11,[70][71][72][73] Third, inactivating STK11/LKB1 mutations or altered STK11/LKB1 expression have also been identified in various sporadic cancers.…”
Section: Molecular Genetics Of Pjs-related Pancreatic Tumorsmentioning
confidence: 99%
“…First, inactivating mutations that either truncate or disrupt the kinase activity of the protein encoded by this gene are detected in the majority but not all cases of PJS. [6][7][8][60][61][62][63][64][65][66][67][68][69] Second, dominant inheritance of a mutant STK11/LKB1 allele coupled with LOH or somatic mutation of the remaining wild-type STK11/LKB1 allele has been documented in PJS patients with various malignancies. 10,11,[70][71][72][73] Third, inactivating STK11/LKB1 mutations or altered STK11/LKB1 expression have also been identified in various sporadic cancers.…”
Section: Molecular Genetics Of Pjs-related Pancreatic Tumorsmentioning
confidence: 99%
“…patients with the syndrome, the normal allele of STK11/LKB1 was lost (104,105).Genetic heterogeneity, like in Carney complex, is possible in PJS; in ours and other laboratories, kindreds with this syndrome have been found that either do not link to the reported locus or do not have STK11/LKB1 mutations (106,107). Another locus for PJS has been proposed on the long arm of chromosome 19 (19q13) (106).…”
Section: Peutz-jeghers Syndromementioning
confidence: 60%
“…O gen de susceptibilidade da SPJ codificado por STK11 (expressa em serino/theorinine quinase, também chamado LKB1), foi identificado em famílias com a síndrome. Resultados confirmam o mapeamento do locus comum no 19p13.3 mas também sugere a existência na minoria das famílias de um locus potencial, no 19q13.4 13 .…”
Section: Discussionunclassified
“…Os avanços das pesquisas genéticas permitiram a identificação dos gens envolvidos nas mutações cromossômicas responsáveis pela malignização dos pólipos e melanose 13,14,15 .…”
Section: Introductionunclassified